Mathematical Modelling of Crime Rate and Prison Population in Nigeria - Ebelechukwu, Okorie Charity; Maina, John Blessing; Chinonye, Nwoke Francisca (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2024)
Human beings and society are susceptible to criminality and so criminality can be likened to an oil that is capable of staining a very white garment when it comes in contact with the white garment. That is why no society can claim to be completely free from crime. The types of criminal behavior depend on the social and economic development of a given society. It is therefore not unexpected that a society at a low level of development tends to experience an upsurge in the rate of violent crimes such as armed robbery, politically motivated killings, the use of illegal weapons, ethnic and religious clashes, and the like. To examine the relationship between the crime rate and the number of prison inmates in Nigeria. Secondary data was used in this study. The data were on various crimes committed within the period of one year and the data were collected from the National Bureau of Statistics. Multiple linear regression modelswere used to carry out the analysis. The result it shows that the top five states with the highest number of criminals and prison populations are Lagos, Rivers, Delta, Abuja, and Kano States.